Fecundity of Sqalius orpheus from the rivers Stryama and Chepinska - Kolev, Vasil (Macedonian Journal of Ecology and Environment, 2021)
This paper presents the results of a study of the reproductive biology of Orpheus dace from the rivers Stryama and Chepinska of the Maritsa River basin, Bulgaria. The material is collected in the spring and autumn of 2011. Totally 312 fish were captured by electrofishing. The study found that some male fish mature sexually in their first year, while females reached sexual maturity in their second year. In the river Stryama, Orpheus dace fecundity varies from 825 to 120252 eggs; average fecundity is 18438 eggs. In the Chepinska River, fecundity is between 3552 and 52416 eggs. Average fecundity of fish from the Chepinska River is 17917 eggs. Absolute fecundity is positively correlated with an increase in fish length and weight. Orpheus dace fecundity also increases with age. For both rivers, five-year-old fish have the highest fecundity rates.